Using Blockchain as a Project Management Device - AL TEKREETI, ANAS (2020)
Blockchain technology is a revolutionary computing innovation. Blockchain technology allows people and companies to make agreements and store information safely without a middleman or entity (Novotny, 2018). It is groundbreaking technology that changes the communication methods of people and organizations across borders. Hence, the aim of this research is to propose an integrated framework for introducing Blockchain technology in the Project Management profession. The paper focuses on the using and applying blockchain tech in construction PM practices. This research paper proposes using blockchain technology in the construction field using the smart contract functionalities. It is expected that the blockchain- based solutions and platforms can make significant contributions to construction projects. The goal is to illustrate how UAE construction companies can implement blockchain technology, to create value addition and other improvements to overcome obstacles facing the industry. The research findings showed that PM can be Impacted by the introduction of Blockchain Technology, especially via smart contract functionalities. It also shows that blockchain smart contracts can be used in certain areas of PM. Overall, Nakamoto creates an amazing P2P system that lets users transfer Bitcoin directly, which does not need the presence of an intermediate figure. The focus is to minimize the broken trust digitally, with the concept of the blockchain. Some people believe that blockchain can move societies to operate digitally. It is a blend of old technologies already existing for a long time. For example, smart contracts are a blockchain based solution that involves linking applications to blockchain (Risius & Spohrer, 2017). It is architecturally decentralized, in the Blockchain. Blockchain is a groundbreaking technology that changes the communication methods of people and organizations across borders. a private blockchain is an invitation-only network governed by a single entity (Yang et al, 2020). Participants would need to gain permission into the network, to access the blockchain. In this paper, a blockchain-based model is used to show that a Blockchain infrastructure can be applied in Project Management (PM). The model is based private cloud infrastructure (i.e. private blockchain). In other words, the characteristics are established on access control mechanisms, regarding sharing project information (Erhan et al, 2019). With this infrastructure, a company has control over who has access to project aspects (Erhan et al, 2019). It can also disperse any or all parts of project information (Erhan et al, 2019). Since it is blockchain-based, carrying out obligations does not require a managing authority. Hence, the data and information are under the authority of the data owner and the sharing of data cannot be altered or removed, without the permission of the project owner (Erhan et al, 2019). Furthermore, the greater demand for blockchain technology justifies the need for block-chain based solutions, such as smart contracts because these solutions are more effective and dependable approaches that can modernize construction PM, especially in the UAE. For this reason, this study can help researchers further uncover critical areas in construction PM that were deemed too complicated or unexplorable to integrate with blockchain technology. Overall, researchers will be informed and guided (by the recommended approaches derived from the research findings) on what factors should be emphasized, to further incorporate blockchain-based solutions into various UAE industries. It is important to have an effective information platform that can 1) gather project information; and 2) provide information (from planning to closing) to relevant parties (Teresko, 2004). It also key that this ‘platform’ allows information to be open, transparent, and comprehensive, especially for complex projects (Teresko, 2004). This is where the technological power of blockchain technology and block-chain based solutions can revolutionize project management. This research paper proposes applying blockchain technology in construction projects through smart contract functionalities. It is expected that the blockchain- based solutions and platforms can make significant contributions to construction projects. The research methodology utilizes the use of both secondary and primary sources. It applies a literature review approach, which involved finding and identifying relevant articles related to the topic, to review and analyze. It also utilizes a survey questionnaire to gain more insight into the overall attitudes towards the technology. Specifically, it measures attitudes and investments about using blockchain in the UAE. The research paper examines the impact of blockchain technology on project management practices in three phases. First, it discusses the fields of Construction and Project Management (PM) before the creation and evolution of blockchain technology. Second, it examines the project life cycle & standard PM approach as well as the effective implementation of life cycle management (LCM) in construction projects. Third, it conveys that the applying blockchain in the construction industry means improving PM. The goal is to illustrate how UAE construction companies can implement blockchain technology, to create value addition and other improvements to overcome obstacles facing the industry.